From SuperTIGER to TIGERISS ... - Rauch, B. F.; Zober, W. V.; Abarr, Q.; Akaike, Y.; Binns, W. R.; Fernandez-Borda, Roberto; Bose, R. G.; Brandt, T. J.; Braun, D. L.; Buckley, J. H.; Cannady, Nicholas; Coutu, S.; et al. (MDPI, 2024)
The Trans-Iron Galactic Element Recorder (TIGER) family of instruments is optimized to measure the relative abundances of the rare, ultra-heavy galactic cosmic rays (UHGCRs) with atomic number (Z) Z ≥ 30. Observing the UHGCRs places a premium on exposure that the balloon-borne SuperTIGER achieved with a large area detector (5.6 m²) and two Antarctic flights totaling 87 days, while the smaller (∼1 m²) TIGER for the International Space Station (TIGERISS) aims to achieve this with a longer observation time from one to several years. SuperTIGER uses a combination of scintillator and Cherenkov detectors to determine charge and energy. TIGERISS will use silicon strip detectors (SSDs) instead of scintillators, with improved charge resolution, signal linearity, and dynamic range. Extended single-element resolution UHGCR measurements through ₈₂Pb will cover elements produced in s-process and r-process neutron capture nucleosynthesis, adding to the multi-messenger effort to determine the relative contributions of ...